Validation of Digital Learning Media to Improve the Basic Literacy Skills of Low-Grade Elementary School Students - Meila Yufriana Devi; Rusdinal Rusdinal (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research was motivated by the low literacy ability of students caused by less interesting learning media. This study aims to create and know the validation of digital learning media to improve students' basic literacy skills in integrated thematic learning in low-grade elementary schools. research starts from the Preliminary Research stage, Prototyping Stage, Assessment Stage. The instruments used in this study were interviews and validation sheets for research samples were students, data collection techniques were carried out using questionnaires and interviews. Based on the problems found in elementary schools, learning media is designed using digital learning media. The following results were obtained after being validated by five validators: content feasibility, presentation feasibility, linguistic feasibility, and graphic feasibility each fall into the excellent category. If the validity value is averaged, then the digital learning media developed is in the range of very valid categories.